Glasgow Blatchford Score of limited benefit for low-risk urban patients: a mixed methods study - Leiman, David A.; Mills, Angela M.; Shofer, Frances S.; Weber, Andrew T.; Leiman, Erin R.; Riff, Brian P.; Lewis, James D.; Mehta, Shivan J. (Endoscopy International Open, 2017)
Background and study aims Most patients with upper gastrointestinal bleeding (UGIB) are hospitalized. Risk-stratifying UGIB with scoring tools may decrease avoidable admissions, thereby reducing the cost of care. We sought to describe how frequently low-risk UGIB patients present to urban emergency departments (ED) and the proportion who are admitted to examine how incorporating risk scores into decision support might diminish healthcare utilization in this population.Patients and methods This is a retrospective cohort study of ED patients presenting from 2009 – 2013 to three urban hospitals that do not use electronic UGIB decision support. We used ED disposition diagnosis codes (ICD-9) to identify patients followed by manual chart review for verification and additional data collection. Patients with a Glasgow Blatchford Score (GBS) of 0 were classified as low risk. We also surveyed ED physicians at these hospitals to assess their beliefs about UGIB decision support.Results Over the study period, 66 patients (13.2 per year) presented to the ED with low-risk UGIB. Of these, 10 patients (15.2 %) were admitted and none required endoscopic hemostasis. Most survey respondents (55.6 %, n = 20) were aware of UGIB risk scores but a minority (19.4 %, n = 7) used one.Conclusions Low-risk UGIB patients infrequently present to the ED and only a minority are admitted. Despite advocacy to incorporate decision support into routine clinical care, ED physicians independently identified low risk patients. There is insufficient evidence to suggest the magnitude of this problem is large enough to warrant implementation of decision support for low risk UGIB.